Experimental analysis of unidirectional oil palm empty fruit bunch fibre-reinforced polymer composites and crash performance using finite element method - Hassan, Cik Suhana (2018)
The overall objective of this research was to analyze the mechanical properties of unidirectional oil palm empty fruit bunch (OPEFB) fibre reinforced polymer composites and simulating their impact failure response using finite element analysis. The work has primarily focused on the fabrication of unidirectional OPEFB fibre reinforced polymer composites using hand lay-up and compression moulding technique employing Epoxy resin and Polypropylene (PP), respectively. The mechanical properties of the OPEFB fibre/polymer composite have been experimentally characterized by varying the fibre orientation angle by 0°, 45° and 90°. Fibre weight ratio was varied by 25%, 35% and 45% for OPEFB fibre/PP composite. Tensile, flexural and impact strength test conducted in accordance to ASTM D638, ASTM D70 and ASTM D6110, respectively. Superior tensile and flexural strengths were observed for the unidirectional OPEFB fibre/epoxy composite with 0° fibre orientation angle, with increases by of around 30% and 216%, respectively, as compared to pure epoxy. Unidirectional OPEFB fibre/PP composites with fibre loading of 35% and 0° fibre orientation was observed to provide the highest tensile strength. There was an increase of around 130% in the tensile strength as compared to pure PP. The greatest resistance to flexural and impact on the other hand were depicted by the 0° oriented OPEFB fibre/PP composites with fibre loading of 25% and 45%, respectively. The flexural and impact strength were found to be better by 328% and 52%, respectively as compared to pure PP. A finite element modeling was developed for predicting the behavior of the OPEFB fibre/polymer composite using the MAT 54/55 material model that is implemented in the LS-DYNA explicit finite element code. The finite element results were validated against the experimental finding. Good correlations with error lesser by 15% were observed between the simulation and the experimental results. Crash performance of the OPEFB fibre/polymer composite as bumper material has been investigated using finite element analysis. The crash was conducted as frontal impact collision with low velocity impact of 4 km/hr. The specific energy absorption (SEA) of the composites bumper part was found to be comparable with the conventional material used for the bumper. The SEA performance of the unidirectional OPEFB fibre/epoxy composites bumper beam was found to be improved by of around 52% as compared to the conventional Aluminum bumper beam. It was also found that there was an increase by 8.34% in the SEA performance of the unidirectional OPEFB fibre/PP composites bumper fascia as compared to pure PP bumper fascia.